2021
DOI: 10.4103/ijmy.ijmy_134_21
|View full text |Cite
|
Sign up to set email alerts
|

Sera from Patients with Tuberculosis Increase the Phagocytic-Microbicidal Activity of Human Neutrophils, and ESAT-6 is Implicated in the Phenomenon

Abstract: Background: It has been reported that sera from patients with active pulmonary tuberculosis (APT) induced nuclear changes in normal neutrophils that included pyknosis, swelling, apoptosis, and production of extracellular traps (NETs). Similar changes were observed with some sera from their household contacts but not with sera from healthy, unrelated individuals. It was suggested that those sera from household contacts that induced neutrophil nuclear changes might correspond to people with subclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Our findings revealed no significant induction of NETs by ESAT-6 and CFP-10 in vitro , which aligns with the observations reported by Rojas-Espinosa et al. ( 50 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings revealed no significant induction of NETs by ESAT-6 and CFP-10 in vitro , which aligns with the observations reported by Rojas-Espinosa et al. ( 50 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previously, Rojas et al. demonstrated that a concentration of 10µg/mL of Mtb soluble recombinant protein ESAT-6 was effective in inducing visible changes in the nuclear morphology of neutrophils ( 50 ). Furthermore, in immunization studies, PE/PPE antigens have been delivered at a concentration of 10µg/mL ( 51 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, necrosis by neutrophils depends on ROS and was blocked when inhibiting MPO, thus restoring the mechanisms for mycobacterial growth control by macrophages ( Dallenga et al, 2017 ). Furthermore, Rojas-Espinosa et al (2021) observed morphological and functional changes in the nuclei of neutrophils from blood from TB patients including DNA extrusion, chromatin decondensation and nuclear swelling, suggesting that M.tb infection may induce NETosis. Nevertheless, recombinant proteins ESAT-6 and CFP-10, while inducing nuclear changes in stimulated neutrophils, did not activate formation of NETs ( Rojas-Espinosa et al, 2021 ).…”
Section: Mtb Recognition By Neutrophilsmentioning
confidence: 94%
“…Furthermore, Rojas-Espinosa et al (2021) observed morphological and functional changes in the nuclei of neutrophils from blood from TB patients including DNA extrusion, chromatin decondensation and nuclear swelling, suggesting that M.tb infection may induce NETosis. Nevertheless, recombinant proteins ESAT-6 and CFP-10, while inducing nuclear changes in stimulated neutrophils, did not activate formation of NETs ( Rojas-Espinosa et al, 2021 ). Conversely, Francis et al (2014) suggested in their study that ESAT-6-treated necrotic neutrophils produced NETs in a Ca 2+ dependent manner with co-localization of ESAT-6 and MPO, supporting a role for ESX-1 in NET formation.…”
Section: Mtb Recognition By Neutrophilsmentioning
confidence: 94%